(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
It didn’t take long for the WhatsApp instant messenger to become widely used among college and university students. WhatsApp is an instant messaging app for smartphones that is available all over the world. When using WhatsApp, you can send and receive multimedia files. WhatsApp makes it simple to share media with friends and family for free, including photos, audio, and video. That so many high school pupils are using WhatsApp suggests that social media technology is changing. Almost no college student does not have access to an instant messaging program like WhatsApp on their mobile device or computer. Schools and institutions have looked into how WhatsApp can help students establish a strong social media presence. Students think of WhatsApp as a tool for transferring resources, improving work habits, and promoting vital context-free education. Most of them have access to the Internet, so they can use WhatsApp to establish a useful learning platform for themselves. Almost everyone has a cell phone with them at all times. The WhatsApp group provides a new route to higher education to fulfill the needs of today’s college students. Students were said to be more engaged in their own learning process when using WhatsApp, which could lead to higher long-term retention. Teachers have the option of working with students who have any combination of the four abilities. Different assignments and activities must be designed to address different study styles. One of the most useful features of WhatsApp is its ability to create a private group of students who may communicate with one other as well as their teacher and the rest of the community.